2001
DOI: 10.1016/s0042-6989(00)00205-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation of chromatic sensitivity across the life span

Abstract: Thresholds were measured along three directions in color space for detecting an equiluminant color change of a set of bars embedded in a larger field of spatio-temporal achromatic noise for observers ranging in age from 3 months to 86 years. Pre-verbal observers were assessed with a forced-choice preferential-looking technique while older observers responded orally or manually. Over the life span, thresholds could be described along each color axis tested by a curve with two trends. Thresholds decreased with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
150
3
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(178 citation statements)
references
References 38 publications
15
150
3
10
Order By: Relevance
“…Because cone outer segment length decreases with retinal eccentricity (Polyak, 1941), photopigment OD is maximal in the foveola and decreases with eccentricity (Pokorny et al, 1976;Marcos et al, 1997). It is not known whether outer segment length varies with age, but a central question in this study was whether there are senescent changes in photopigment OD that may account for age-related losses in the sensitivity of M-and L-cone pathways (Werner et al, 2000;Knoblauch et al, 2001). Quantitative modeling indicates that much of the senescent loss in cone sensitivity is due to degradations that are mathematically equivalent to a loss in quantal efficiency and0or an elevation in neural noise (Schefrin et al, 1992(Schefrin et al, , 1995.…”
Section: Introductionmentioning
confidence: 93%
“…Because cone outer segment length decreases with retinal eccentricity (Polyak, 1941), photopigment OD is maximal in the foveola and decreases with eccentricity (Pokorny et al, 1976;Marcos et al, 1997). It is not known whether outer segment length varies with age, but a central question in this study was whether there are senescent changes in photopigment OD that may account for age-related losses in the sensitivity of M-and L-cone pathways (Werner et al, 2000;Knoblauch et al, 2001). Quantitative modeling indicates that much of the senescent loss in cone sensitivity is due to degradations that are mathematically equivalent to a loss in quantal efficiency and0or an elevation in neural noise (Schefrin et al, 1992(Schefrin et al, , 1995.…”
Section: Introductionmentioning
confidence: 93%
“…Although these changes could be due to maturational effects, this is unlikely, given the stability of color perception across the lifetime (Knoblauch, VitalDurand, & Barbur, 2001;Petzold & Sharpe, 1998;Roorda & Williams, 1999). Absolute chromatic sensitivities vary over the lifespan (e.g., Banks & Bennett, 1988), but psychophysical threshold measurements indicate that relative sensitivities along the three primary chromatic axes (protan, deutan, and tritan) change little, if at all, from the first 3-4 months of life to 86 years of age (Knoblauch et al, 2001). Other research on hue discrimination performance as a function of age found only slight differences between the ages of 4 and 25 years (Petzold & Sharpe, 1998).…”
Section: An Ecological Account Of Individual Differencesmentioning
confidence: 99%
“…Red-green (RG) and yellow-blue (YB) mechanisms act independently at threshold [20], but it is generally believed that aging affects preferentially the YB mechanism [21,22]. Although several studies have shown that color vision deteriorates with advancing age [23,24], some controversy remains as to whether normal aging affects more the YB mechanism [25]. Diseases of the eye, such as diabetes, tend to affect uniformly both RG and YB mechanisms, although the loss of YB sensitivity precedes RG in early stage age-related macular degeneration [26].…”
Section: Introductionmentioning
confidence: 99%